ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIS PESERTA DIDIK DITINJAU DARI PERBEDAAN GENDER DAN USIA - Samsuriadi; Nur Rohmah Lestari (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The purpose of this study is to describe critical thinking skills in terms of gender and age differences. This research uses a qualitative descriptive research type. The subjects in this study were students in class X MIPA SMA NW Suralaga who had UTS scores above the KKM, namely 65 and aged between 14-16 years. After obtaining 20 subjects, these subjects were then given a problem-solving test about mathematical critical thinking skills and from the results of the test the subjects were grouped based on the level of very high, high, low and very low critical thinking skills. Next, representatives from each category were selected as respondents representing other students. Data collection techniques using written tests, interviews, and documentation. Data analysis in this study is using data reduction, data presentation and drawing conclusions. The results of this study indicate that in general there is no significant difference in the critical thinking skills of men and women. Then based on age, it does not show that the older a person is, the higher the ability to think critically.